A New ZVT Snubber Cell for PWM-CCM-PFC Boost Converters - Yildirmaz, Suat; Bodur, Haci (IEEE, 2015)
In this study, a new Zero Voltage Transition (ZVT) snubber cell is proposed. Zero Voltage Transition (ZVT) turn on and zero voltage switching (ZVS) turn off are achieved for the main switch. Also, the auxiliary switch is turned on with zero current switching (ZCS) and turned off with ZVS. The main advantage of this snubber cell is that it reduces the current stresses of the auxiliary circuit components significantly. The proposed snubber cell, which has been used in Pulse Width Modulated (PWM) Continues Current Modulation (CCM) - Power Factor Correction (PFC) boost converter, has been verified both by simulation software and experimentally.
Keywords: Soft switching; zero voltage switching; zero voltage transition; power factor correction; boost converter; POWER-FACTOR CORRECTION; FLYBACK CONVERTER; AC/DC CONVERTER; VOLTAGE; RECTIFIER; TOPOLOGY; FAMILY; Energy & Fuels; Engineering